COLLOCABILITY AS A MEANS OF CREATING EXPRESSIVE WORD USAGE (Proceedings of Southern Federal University. Philology, 2012)
Vlavatskaya M.V.Keywords: word combinability, collocability, expressive word, connotational semantic features, expressive potential.The article touches upon one of the functions of word combinability - collocabil- ity as a means of creating expressive word usage. Any expressive word possesses one or a set of connotational semantic features (emotive charge, evaluation, imagery, intensity, stylistic reference). At the same time only the context expressed by collocated words is the environment, in which the expressive potential of the word is realized in the most exhaustive way.